A standard for terminology in chronic pelvic pain syndromes: A report from the chronic pelvic pain working group of the international continence society. Issue 4 (26th August 2016) - Doggweiler, Regula; Whitmore, Kristene E.; Meijlink, Jane M.; Drake, Marcus J.; Frawley, Helena; Nordling, Jørgen; Hanno, Philip; Fraser, Matthew O.; Homma, Yukio; Garrido, Gustavo; Gomes, Mario J.; Elneil, Sohier; et al.
Abstract : Aims: Terms used in the field of chronic pelvic pain (CPP) are poorly defined and often confusing. An International Continence Society (ICS) Standard for Terminology in chronic pelvic pain syndromes (CPPS) has been developed with the aim of improving diagnosis and treatment of patients affected by chronic pelvic pain syndromes. The standard aims to facilitate research, enhance therapy development and support healthcare delivery, for healthcare providers, and patients. This document looks at the whole person and all the domains (organ systems) in a systematic way. Methods: A dedicated working group (WG) was instituted by the ICS Standardisation Steering Committee according to published procedures. The WG extracted information from existing relevant guidelines, consensus documents, and scientific publications. Medline and other databases were searched in relation to each chronic pelvic pain domain from 1980 to 2014. Existing ICS Standards for terminology were utilized where appropriate to ensure transparency, accessibility, flexibility, and evolution. Consensus was based on majority agreement. Results: The multidisciplinary CPPS Standard reports updated consensus terminology in nine domains; lower urinary tract, female genital, male genital, gastrointestinal, musculoskeletal, neurological aspects, psychological aspects, sexual aspects, and comorbidities. Each is described in terms of symptoms, signs and further evaluation. Conclusion: The document presents preferred terms and definitions for symptoms, signs, and evaluation (diagnostic work‐up) of female and male patients with chronic pelvic pain syndromes, serving as a platform for ongoing development in this field. Neurourol. Urodynam. 36:984–1008, 2017 . © 2016 Wiley Periodicals, Inc.